Speech Act Analyzing in Top Gun: Maverick Film - Irsya Rachmat Riyadi (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2023)
This article discussed the identification of speech acts through several dialogues between characters in Top Gun: Maverick. The aim of this study is to find out the types of speech acts used in Top Gun: Maverick. The data were utterances suspected to have speech acts uttered by this film's characters. The method used in this study is a qualitative descriptive method to classify speech acts used in Top Gun: Maverick. This study found three types of speech acts used in the Top Gun: Maverick film, namely expressive speech acts preferred form found one data and misery found one data, Perlocutionary speech acts form rejection found two data and directive speech acts.